2018
DOI: 10.3390/su10030682
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Academic Discipline of Knowledge Management

Abstract: Abstract:The aim of this paper was to evaluate the research status of knowledge management (KM) and identify the characteristics of KM in the literature. We selected and studied in detail 7628 original research articles from the Web of Science from 1974 to 2017. Although many studies have contributed to the evolution of the KM domain, our results showed that a comprehensive bibliometric and visualization investigation was required. The literature on KM has grown rapidly since the 1970s. The United States of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 63 publications
1
28
0
7
Order By: Relevance
“…Besides, while the literature on the background of knowledge-sharing has been continuously growing since 2000, the results of studies are becoming more complex and cross-disciplinary, especially in works done on the motivators of online knowledge-sharing at the individual level [54][55][56] and the impact of knowledge-sharing on resource-or capability-based competitive advantages at the firm level [90,91]. Prior research has stressed investigations of the relationships between knowledge-sharers within a group (e.g., opinion leaders) and their influence on other online group users (e.g., in-group members) in the context of online communities; however, opinion leaders' cross-group influence on knowledge-sharing engagement at the group level has rarely been studied thoroughly [92].…”
Section: Online Groups: In-groups and Out-groupsmentioning
confidence: 99%
“…Besides, while the literature on the background of knowledge-sharing has been continuously growing since 2000, the results of studies are becoming more complex and cross-disciplinary, especially in works done on the motivators of online knowledge-sharing at the individual level [54][55][56] and the impact of knowledge-sharing on resource-or capability-based competitive advantages at the firm level [90,91]. Prior research has stressed investigations of the relationships between knowledge-sharers within a group (e.g., opinion leaders) and their influence on other online group users (e.g., in-group members) in the context of online communities; however, opinion leaders' cross-group influence on knowledge-sharing engagement at the group level has rarely been studied thoroughly [92].…”
Section: Online Groups: In-groups and Out-groupsmentioning
confidence: 99%
“…They found that the top two subject terms were: "information resources management" (555 articles) and "information science" (417 articles). More recently, Wang, Zhu, Song, Hou, and Zhang (2018) found that "Information Science/Library Science" was second (1723 articles, 22.6% of the total) in terms of being in the top 30 KM categories ranked by the number of publications. "Management" was the first subject category with 2334 articles (30.6% of the total).…”
Section: Where We Have Been--km and Information Science In The Pastmentioning
confidence: 99%
“…"Management" was the first subject category with 2334 articles (30.6% of the total). Wang et al (2018) also visualized the academic discipline of KM by showing the co-words network of author keywords in KM articles published from 1974-2017. Goswami and Agrawal (2018) looked at where KM articles were published in 11 key journals over the years.…”
Section: Where We Have Been--km and Information Science In The Pastmentioning
confidence: 99%
“…KM is crucial for organizations that want to achieve effectiveness and efficiency. KM has proved to be useful to organizations in a fast-changing environment [6,7]. This paper is divided into six sections.…”
Section: Introductionmentioning
confidence: 99%